THE EFFECT OF GOOD CORPORATE GOVERNANCE AND FIRM SIZE ON FINANCIAL PERFORMANCE WITH CAPITAL STRUCTURE AS A MODERATING VARIABLE (EMPIRICAL STUDY OF REGISTERED MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE IN 2016-2018) - Pulungan, Faisal Fadly (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to examine and analyse the effect of good corporate governance with indicators consisting of managerial ownership, institutional ownership, board of commissioners, board of directors, and audit committee, and firm size simultaneously affecting the financial performance of manufacturing companies listed on the Indonesia Stock Exchange and also to test and analyse whether the ability of capital structure can moderate the relationship between variables of good corporate governance with indicators consisting of managerial ownership, institutional ownership, board of commissioners, board of directors, and audit committee, and firm size in manufacturing companies registered in Indonesia Stock Exchange. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange. From 132 companies as population, 20 samples were taken as determined by purpose sampling method. The results of hypothesis testing indicate that managerial ownership, institutional ownership, board of commissioners, board of directors, audit committee, and firm size together or simultaneously have a significant effect on financial performance. The results of the moderating test with the interaction test show that the capital structure is significant in moderating the effect of institutional ownership on financial performance and the capital structure is not in moderating the relationship between managerial ownership variables, the board of commissioners, the board of directors, and the audit committee, and firm size on financial performance.